1993
DOI: 10.3109/00016349309013342
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis in pregnancy treated with yoghurt

Abstract: As various drugs might have an effect on the fetus during pregnancy, the use of drugs should be minimized in the pregnant woman. Since bacterial vaginosis (BV) can be associated with prematurity and postpartum complications, we searched for alternative therapy for its cure during pregnancy. Commercial yoghurt incorporates both factors necessary for maintaining the protective mechanism of the vagina, vaginal pH and lactobacillus. A total of 32 women with BV in the first trimester of pregnancy were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 10 publications
(6 reference statements)
0
28
0
Order By: Relevance
“…In normal vaginal microbiota, a huge number of Lactobacillus bacteria exist, which prevent the colonization and proliferation of pathogenic microorganisms through several ways, such as competition for nutrients and adherence, production of H 2 O 2 [34], bacteriocins [35] and lactic acid, which is mainly responsible for the protective acidic pH of the vagina [36]. Several clinical studies showed that intravaginal administration of Lactobacillus acidophilus resulted in a significantly increased number of recoveries compared to treatments with placebo, acetic acid or no treatment [37][38][39][40]. Furthermore, a recent review drew attention to the increased importance of probiotic treatment for prevention of bacterial vaginosis so that more serious complications can be avoided [41].…”
mentioning
confidence: 99%
“…In normal vaginal microbiota, a huge number of Lactobacillus bacteria exist, which prevent the colonization and proliferation of pathogenic microorganisms through several ways, such as competition for nutrients and adherence, production of H 2 O 2 [34], bacteriocins [35] and lactic acid, which is mainly responsible for the protective acidic pH of the vagina [36]. Several clinical studies showed that intravaginal administration of Lactobacillus acidophilus resulted in a significantly increased number of recoveries compared to treatments with placebo, acetic acid or no treatment [37][38][39][40]. Furthermore, a recent review drew attention to the increased importance of probiotic treatment for prevention of bacterial vaginosis so that more serious complications can be avoided [41].…”
mentioning
confidence: 99%
“…In a related field, four studies (Krauss-Silva et al, 2011;Neri et al, 1993;Nishijima et al, 2005;Thiagarajan, 1998) have investigated the impact of a daily dose of probiotics, administered either orally or vaginally, on rates of bacterial vaginosis specifically in pregnant women.…”
Section: Probiotics In Pregnancymentioning
confidence: 99%
“…In an unblinded trial by Neri and colleagues (15), 84 pregnant women with bacterial vaginosis were randomized to a twicedaily 7-day dose of yogurt douches (n ϭ 32), acetic acid tampons (n ϭ 32), or no treatment (n ϭ 20). Two months after treatment, 88% of women using yogurt douches and 38% of women using acetic acid tampons compared with 5% of women without treatment were free of bacterial vaginosis (P Ͻ .05 between all groups).…”
Section: Lactobacilli Recolonization: Vaginal Administrationmentioning
confidence: 99%